Analysing the importance and impact of cloud computing on organization's performance management during economic crises. (2022) - Wisetsri, Worakamol; Franklin John, S.; Prasad, Arun B.; Garg, Shaifali; Khaja Mohiddin, Md.; Bhaskar, Bandi
Abstract: Organization performance management have difficulties in providing the required funding for instructional, research and development activities given the present financial crisis and the increasing requirements. The purpose of this article is for colleges to identify options to the usage of IT to make them more agile and save. A careful examination of the current Cloud Computing studies as an alternative to IT, security management were the conceptual framework. In addition to the authors of IT and higher education, it takes into account best practices for cloud computing used in organization management. The paper starts with a brief overview to cloud computing at organization performance management, which refers to the main outcomes that have been achieved. At addition, the proposal for an adoption plan provides a beginning point for cloud computing in organization management. The approach consists of five steps, focusing on information assessment and processes/functions/applications from many major academic organization managements on a range of essential criteria, while at the same time building a match between any of these features and the cloud market concepts. The results achieved encourage and encourage the use of cloud solutions in organization performance management by enhancing knowledge in this sector and offering a gentle introduction suitable for the organization of the university. The suggested model takes into consideration the architectural and criteria of the university, such as mission, availableness, applications significance, and mission, sensitivity, secrecy, integrity and accessibility, in order to be practically usable.